Factors influencing performance of housing loan in Malaysian Commercial Banks / Yuslizawati Mohd Yusoff and Nor Hazila Ismail - Mohd Yusoff, Yuslizawati; Ismail, Nor Hazila (2010)
This paper empirically investigates the factors that influencing the performance of housing loan in Malaysian commercial bank industry. The commercial banks, as part of financial institution in Malaysia have played an important role in order to improve as well as to expand the housing loan industry in Malaysia banking sector. However, the successful and the performance of the housing loan industry of that institution depend on several factors. The data for this study will be collected for 36 months started from January 2006 until December 2008. The data from all 22 commercial banks were aggregated and combined in order to acquire the total performance of the housing loan product in that particular industry. In order to see the correlation between the dependent and independent variables, we will apply Multiple Linear Regression method. The performance of housing loan will be measured in terms of monthly disbursement volume. The independent variables are; interest rate, repayment and supply. The findings indicate that the three variables show significantly related with the housing loan performance.